Strong temper and complete detachment: History and memory of teachers in the sertÃo paulista (1932-1960) - Mariano, Jorge Luís Mazzeo; Ribeiro, Arilda Ines Miranda [UNESP] (FapUNIFESP (SciELO), 2018)
This article shows the primary teachers' role in building the foundations of school culture in the face of the rudeness and precariousness of the extreme west of São Paulo, between the 1930s and 1960s. For this purpose, the research resorted to the official documentation of the period and to the oral reports of some teachers who worked in that region. Teachers had to face the difficulties inherent in starting their careers and teaching in improvised real estate for educational purposes, as part of a kind of “internship” in the rural area imposed by the state. In dealing with the precariousness of school facilities and the state's inspection presence, these educators constructed the school culture of the schools in which they taught, improvising with the resources they possessed.
TÊmpera forte e completo desprendimento: HistÓria e memÓria das docentes no sertÃo paulista (1932-1960)
Keywords: Extreme west of São Paulo; Isolated school; Primary teachers; Rural area